2010
DOI: 10.1016/j.ijhcs.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Human-centred design methods: Developing scenarios for robot assisted play informed by user panels and field trials

Abstract: This article describes the user-centred development of play scenarios for robot assisted play, as part of the multidisciplinary IROMEC 1 project that develops a novel robotic toy for children with special needs. The project investigates how robotic toys can become social mediators, encouraging children with special needs to discover a range of play styles, from solitary to collaborative play (with peers, carers/teachers, parents, etc.). This article explains the developmental process of constructing relevant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 37 publications
2
53
0
5
Order By: Relevance
“…Common approaches guided by this perspective (Rahimi &Karwowski, 1990 andRobins et al, 2010 for example) see the human as central in the interaction paradigm; the human leads the interaction, communicates the task to be done and defines the intentionality of the situation. Conversely, the robot is a passive, albeit intelligent, participant at this level of the interaction and is the Task Completer; which is problematic for social robotics.…”
Section: Related Literaturementioning
confidence: 99%
“…Common approaches guided by this perspective (Rahimi &Karwowski, 1990 andRobins et al, 2010 for example) see the human as central in the interaction paradigm; the human leads the interaction, communicates the task to be done and defines the intentionality of the situation. Conversely, the robot is a passive, albeit intelligent, participant at this level of the interaction and is the Task Completer; which is problematic for social robotics.…”
Section: Related Literaturementioning
confidence: 99%
“…Therefore, prior research in this particular field is relatively minimal [2]. Most of the current research studies robots that participate in social human interactions as companions [3]. Find-andfollow is a multidisciplinary field of robotics in which a mixture of subjects such as perception, robot navigation and HRI intervenes.…”
Section: Introductionmentioning
confidence: 99%
“…Various research studies have shown that autistic children' s attention can be engaged better when they communicate with a robot rather than with a human [1,2]. These findings led to the development of new therapeutic approaches where robots are used as mediators.…”
Section: Introductionmentioning
confidence: 99%